The Effect of the Amount and Term of Credit and the Debtor's Business Income on the Repayment of People's Business Credit - Raihan, Muhammad; Susandra, Farizka; Anwar, Saepul (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
This study aims to determine the influence of the loan amount, loan term, and debtor's business income on the repayment of People's Business Credit (KUR) at Bank BRI Unit Cijeruk, Bogor, with the account officer as a moderating variable. Credit repayment refers to the debtor's ability to repay the loan, which affects credit collectability. The study population consists of 2,589 debtors registered at Bank BRI Unit Cijeruk in 2023. From this population, 104 debtors were selected as samples using purposive sampling techniques. The analytical tools used in this study are logistic regression and Moderated Regression Analysis (MRA). The results indicate that the loan amount, loan term, and debtor's business income have a significant impact on KUR repayment. Furthermore, the account officer, as a moderating variable, is proven to moderate the effect of the debtor's business income on KUR repayment. However, the account officer does not moderate the effect of the loan amount and loan term on KUR repayment. These findings highlight the importance of the role of account officers in enhancing the effectiveness of KUR repayment, particularly in the context of the debtor's business income, while they do not provide a moderating effect on the loan amount and loan term.